Tumor-associated macrophages in nanomaterial-based anti-tumor therapy: as target spots or delivery platforms - Zheng, Jixuan; Jiang, Jinting; Pu, Yicheng; Xu, Tingrui; Sun, Jiantong; Zhang, Qiang; He, Ling; Liang, Xiao (Frontiers in Bioengineering and Biotechnology, 2023)
Targeting tumor-associated macrophages (TAMs) has emerged as a promising approach in cancer therapy. This article provides a comprehensive review of recent advancements in the field of nanomedicines targeting TAMs. According to the crucial role of TAMs in tumor progression, strategies to inhibit macrophage recruitment, suppress TAM survival, and transform TAM phenotypes are discussed as potential therapeutic avenues. To enhance the targeting capacity of nanomedicines, various approaches such as the use of ligands, immunoglobulins, and short peptides are explored. The utilization of live programmed macrophages, macrophage cell membrane-coated nanoparticles and macrophage-derived extracellular vesicles as drug delivery platforms is also highlighted, offering improved biocompatibility and prolonged circulation time. However, challenges remain in achieving precise targeting and controlled drug release. The heterogeneity of TAMs and the variability of surface markers pose hurdles in achieving specific recognition. Furthermore, the safety and clinical applicability of these nanomedicines requires further investigation. In conclusion, nanomedicines targeting TAMs hold great promise in cancer therapy, offering enhanced specificity and reduced side effects. Addressing the existing limitations and expanding our understanding of TAM biology will pave the way for the successful translation of these nano-therapies into clinical practice.